Cytogenetics and Molecular Abnormalities in Pediatric Patients with Acute Myeloid Leukemia in a Referral Center in Tehran, Iran - Mahshid Heidary Sadegh; Maniya Mozafari; Mohammad Vasei; Sajjadeh Movahedinia; Marzieh Hosseini; Moeinadin Safavi (Middle East Journal of Cancer)
Background: Acute myeloid leukemia (AML) accounts for 15%-20% of childhood leukemia. A variety of cytogenetic abnormalities have been reported in AML, but it is still debated how these alterations affect patient survival and outcome. We aimed to evaluate the cytogenetic abnormalities of pediatric AML in association with prognosis.Method: In this retrospective cross-sectional study, 46 cases of pediatric AML, diagnosed using French-American-British (FAB) criteria, admitted to a referral center during 2018-2023, who had not yet received chemotherapy, were included. Patients were evaluated for cytogenetic alterations by bone marrow karyotyping and polymerase chain reaction molecular methods. Patients were followed up to evaluate overall survival and recurrence-free survival. Data were analyzed using SPSS software version 23 and chi-square, Mann-Whitney, t-test and Kaplan-Meier tests. P < 0.05 was considered significant.Results: Totally, 19 of 46 (41.3%) patients showed cytogenetic abnormalities. The prevalence of numerical and structural abnormalities was 23.9% and 28.3%, respectively. The most common numerical changes included monosomy 7, loss of chromosome Y, and trisomy 21, as order. The most common structural variants included t(v;11), t(15;17), t(8;21) and del(7q). Those with t(8;21) and t(15;17) or absence of cytogenetic abnormalities had a lower recurrence and death rate as compared with those with unfavorable cytogenetic abnormalities (P = 0.007 and P = 0.002 respectively). White blood cell count was significantly lower in patients with numerical cytogenetic abnormalities than those without.Conclusion: Cytogenetic abnormalities were rather common in pediatric AML. Monosomy 7/del(7q) and chromosome 11 alteration were the most common cytogenetic abnormalities. Presence of abnormalities, other than those known as favorable, were associated with worse survival.